Effectiveness of Moocs-Based Safety Management System Learning Development - Oka, I.G.A. Ayu Mas; Masito, Fitri; Danim, Sudarwan (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The purpose of this study is to test the effectiveness of the safety management system learning method through MOOCs compared to previous learning methods. This research is a type of quantitative descriptive research. The data collection technique is a non-test technique with a research instrument in the form of a response questionnaire. The data in this study were obtained from primary data sources, namely the results of filling out questionnaires by respondents. The research was conducted at the Palembang Aviation Polytechnic in November 2022. The population in this study was 250 Palembang Polytechnic cadets. The research sample was 105 cadets who took the Safety Management System course, which was taken using a purposive sampling technique. The data analysis technique uses the Paired-Samples T-Test with the help of SPSS software. Results research shows that the value of sig. (2-tailed) is less than 0.05, so H0 is rejected and Ha is accepted. So it can be concluded that there is a significant difference between the effectiveness of the MOOC-based SMS learning method and the previous learning method.